Changes in the Cholinergic, Catecholaminergic, Orexinergic and Serotonergic Structures Forming Part of the Sleep Systems of Adult Mice Exposed to Intrauterine Alcohol - Oladiran I. Olateju; Adhil Bhagwandin; Amadi O. Ihunwo; Paul R. Manger (Frontiers Media S.A., 2017)
We examined the effect of chronic prenatal alcohol exposure on certain neuronal systems involved with the sleep-wake cycle of C57BL/6J mice exposed to prenatal alcohol once they had reached 56 days post-natal. Pregnant mice were exposed to alcohol, through oral gavage, on gestational days 7-16, with recorded blood alcohol concentration (BAC)s averaging 1.84 mg/ml (chronic alcohol group, CA). Two control groups, an oral gavage sucrose control group (chronic alcohol control group, CAc) and a non-treated control group (NTc), were also examined. At 56 days post-natal, the pups from each group were sacrificed and the whole brain sectioned in a coronal plane and immunolabeled for cholineacetyltransferase (ChAT), tyrosine hydroxylase (TH), serotonin (5HT) and orexin-A (OxA) which labels cholinergic, catecholaminergic, serotonergic and orexinergic structures respectively. The overall nuclear organization and neuronal morphology were identical in all three groups studied, and resemble that previously reported for laboratory rodents. Quantification of the estimated numbers of ChAT immunopositive (+) neurons of the pons, the TH+ neurons of the pons and the OxA+ neurons of the hypothalamus showed no statistically significant difference between the three experimental groups. The stereologically estimated areas and volumes of OxA+ neurons in the CA group were statistically significantly larger than the groups not exposed to prenatal alcohol, but the ChAT+ neurons in the CA group were statistically significantly smaller. The density of orexinergic boutons in the anterior cingulate cortex was lower in the CA group than the other groups. No statistically significant difference was found in the area and volume of TH+ neurons between the three experimental groups. These differences are discussed in relation to the sleep disorders recorded in children with fetal alcohol spectrum disorder (FASD).